2021
DOI: 10.3389/fphar.2020.601685
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 and COVID-19: A Multidisciplinary Theory of a Multifaceted Therapeutic Target

Abstract: By mapping the clinical pathophysiology of the novel coronavirus disease 2019 (COVID-19) against insights from virology, immunology, genomics, epidemiology and pharmacology, it is here proposed that the pathogen recognition receptor called toll like receptor 9 (TLR9) might have a pivotal role in the pathogenesis of COVID-19. Severe Acute Respiratory Syndrome Coronavirus 2, is causing the greatest global social and economic disruption since world war II. Lack of a vaccine, lack of successful treatment and limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 182 publications
0
59
0
5
Order By: Relevance
“…This, in turn, may trigger other inflammatory signalling pathways and the production of proinflammatory mediators ( 41 , 43 ). The expression levels of TLR9 and levels of endogenous triggers for TLR9 activation are also influenced by diet which has been proposed to contribute to a severe outcome of COVID-19 in vulnerable patients ( 44 ).…”
Section: Physical Inactivity Malnutrition and Covid-19mentioning
confidence: 99%
“…This, in turn, may trigger other inflammatory signalling pathways and the production of proinflammatory mediators ( 41 , 43 ). The expression levels of TLR9 and levels of endogenous triggers for TLR9 activation are also influenced by diet which has been proposed to contribute to a severe outcome of COVID-19 in vulnerable patients ( 44 ).…”
Section: Physical Inactivity Malnutrition and Covid-19mentioning
confidence: 99%
“…NK cells and TLR activity must be inhibited to decrease hyper inflammation and prevent multi-organ complications in the hyper inflammation stage. [242] , [243] , [244] Toll-lik receptor (TLR) activator (PUL-042 CpG) Oxygen therapy mechanical ventilation A ventilator's early employment for mild COVID-19 patients could prevent progressing to more severe lung injury. Mechanical ventilation is lifesaving in severe respiratory failure.…”
Section: Covid-19 Treatment Strategiesmentioning
confidence: 99%
“…Studies have shown that the use of umbilical cord blood-derived or isolated NK cell from healthy donor PBMCs may be helpful to the treatment of COVID-19 in the early of infection. Meanwhile, the activation of pathogen recognition receptors, including toll-like receptors 2, 6, and 9 (TLR2/6/9) by PUL-042 CpG oligodeoxynucleotides (CpG ODNs) in the early stage of COVID-19 infection, particularly on DCs and B cells, leading to innate immune stimulation can be employed as prophylactic or therapeutic [244] . In the hyperinflammation level of COVID-19 infection in vulnerable patients in which the host immune system remains active over a prolonged period, the inhibition of TLR and NK cell pathway can help to prevent or dampen hyperinflammation and multi-organ complications [244] ( Table 2 ).…”
Section: Covid-19 Treatment Strategiesmentioning
confidence: 99%
“…In array analysis, the level of TLR9 was upregulated in response to SARS-CoV infection, even more than other TLRs such as TLR2 and TLR4 [ 105 ]. TLR9 can in fact explain a huge variety of the symptoms observed in COVID-19, and in specific cases be hypothesized as the leading cause of the hyperinflammatory process [ 106 ]. AIM2 can be activated in monocytes infected with SARS-CoV-2 in an antibody mediated manner, causing pyroptotic cell death [ 107 ] and in pangolins, carriers of coronaviruses and together with bats, focus of studies of the SARS-CoV-2 zoonotic transmission to humans, lack the ZBP1 protein [ 108 ].…”
Section: The Mtdna Receptors and Their Role In Inflammatory Processes - Do They Constitute A Possible Link With Sars-cov-2?mentioning
confidence: 99%